Q-switched fiber laser with tungsten disulfide saturable absorber prepared by drop casting method - Razak, Nurul Nadia; Yasin, Moh; Zakaria, Zahriladha; Latiff, Anas A; Harun, Sulaiman Wadi (Photonics Letters of Poland, 2017)
We experimentally demonstrate a passively Q-switched erbium-doped fiber laser (EDFL) operation by using a saturable absorber (SA) based on tungsten disulfide (WS2). By depositing WS2 thin film layer at the end of optical fiber ferrule, we fabricated a SA device. The SA is incorporated into an Erbium-doped fiber laser (EDFL) cavity to generate a Q-switching pulses train operating at 1559.8 nm. As a result, stable passively Q-switched EDFL pulses with maximum output pulse energy of 123.2 nJ, repetition rate of 104.1 kHz, and pulse width of 9.61 us are achieved when the input pump power is 142.1 mW at the wavelength of 980 nm. Full Text: PDF References C. Gao, W. Zhao, Y. Wang, S. Zhu, G. Chen, and Y. Wang, "Passive Q-switched fiber laser with SESAM in ytterbium-doped double-clad fiber", in 27th International congress on High-Speed Photography and Photonics (International Society for Optics and Photonics, 2007). CrossRef M. Ahmed, N. Ali, Z. Salleh, A. Rahman, S. Harun, M. Manaf, et al., "Q-switched erbium doped fiber laser based on single and multiple walled carbon nanotubes embedded in polyethylene oxide film as saturable absorber", Optics & Laser Technology 65, 25 (2015). CrossRef M. A. Ismail, F. Ahmad, S. W. Harun, H. Arof and H. Ahmad, "A Q-switched erbium-doped fiber laser with a graphene saturable absorber", Laser Phys. Lett. 10, 025102 (2013). CrossRef G. Sobon, J. Sotor, J. Jagiello, R. Kozinski, K. Librant, M. Zdrojek, L. Lipinska, and K. M. Abramski, "Linearly polarized, Q-switched Er-doped fiber laser based on reduced graphene oxide saturable absorber", Appl. Phys. Lett. 101, 241106 (2012). CrossRef N. H. M. Apandi, F. Ahmad, S. N. F. Zuikafly, M. H. Ibrahim, S. W. Harun, "Bismuth (III) Telluride (Bi2Te3) topological insulator embed in PVA as passive Q-switcher at 2 micron region", Photon. Lett. of Poland 8, 101 (2016). CrossRef J. Bogusławski, G. Soboń, K. Tarnowski, R. Zybała, K. Mars, A. Mikuła, K. M. Abramski and J. Sotor, "All-polarization-maintaining-fiber laser Q-switched by evanescent field interaction with Sb2Te3 saturable absorber", Optical Engineering 55, 081316 (2016). CrossRef Z. Luo, Y. Huang, M. Zhong, Y. Li, J. Wu, B. Xu, H. Xu, Z. Cai, J. Peng, and J. Weng, "1-, 1.5-, and 2-um fiber lasers Q-switched by a broadband few-layer MoS2 saturable absorber", J. Lightwave Technol. 32, 4679 (2014). CrossRef N. N. Razak, A. A. Latiff, Z. Zakaria and S. W. Harun, "Q-switched Erbium-doped Fiber Laser with a Black Phosphorus Saturable Absorber", Photon. Lett. of Poland 9, 72 (2017). CrossRef D. Mao, Y. Wang, C. Ma, L. Han, B. Jiang, X. Gan, S. Hua, W. Zhang, T. Mei, and J. Zhao, "WS2 mode-locked ultrafast fiber laser", Sci Rep 5, 7965 (2015). CrossRef K. Wu, X. Zhang, J. Wang, X. Li, and J. Chen, "WS2 as a saturable absorber for ultrafast photonic applications of mode-locked and Q-switched lasers", Optics Express 23, 11453 (2015). CrossRef K. Lau, A. Latif, M. A. Bakar, F. Muhammad, M. Omar, and M. Mahdi, "Mechanically deposited tungsten disulfide saturable absorber for low-threshold Q-switched erbium-doped fiber laser", Applied Physics B 123, 221 (2017). CrossRef H. Chen, Y. Chen, J. Yin, X. Zhang, T. Guo, and P. Yan, "High-damage-resistant tungsten disulfide saturable absorber mirror for passively Q-switched fiber laser", Optics Express 24, 16287 (2016). CrossRef J. Lin, K. Yan, Y. Zhou, L. Xu, C. Gu, and Q. Zhan, "Tungsten disulphide based all fiber Q-switching cylindrical-vector beam generation", Applied Physics Letters 107, 191108 (2015). CrossRef H. Chen, Y. Chen, J. Yin, X. Zhang, T. Guo, and P. Yan, "High-damage-resistant tungsten disulfide saturable absorber mirror for passively Q-switched fiber laser", Optics Express 24, 16287 (2016). CrossRef K. Mohamed, B. Hamida, S. Khan, L. Hussein, M. Ahmat, E. Ismail, N. Kadir, A. Latif, S. Harun, "Q-switched erbium-doped fibre laser based on molybdenum disulfide and tungsten disulfide as saturable absorbers," Ukrainian Journal of Physical Optics, 18 (2017). CrossRef